Efektivitas Kinerja Satuan Polisi Pamong Praja dalam Penertiban Pedagang Kaki Lima di Pasar Peureulak Gampong Keude Kabupaten Aceh Timur - Ridwan, Ridwan; Kusmanto, Heri; Warjio, Warjio; Kadir, Abdul (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The purpose of this study was to analyze the effectiveness of the performance and constraints of the Civil Service Police Unit in controlling Street Vendors in Peureulak Market, East Aceh Regency. This study used descriptive qualitative method. The sample in this study amounted to 8 people. Data collection is obtained from interviews, documentation and observation. The results showed that the performance of the Civil Service Police Unit in controlling street vendors in the Peureulak Market in East Aceh Regency was through policing and socialization. Control is carried out in collaboration with various Local Government agencies ranging from the Office, Assets, to the Regent. The socialization was carried out as a Satpol PP function in addition to its main task of controlling, so that Satpol PP members had to be able to communicate well with street vendors. The municipal police conduct curbing if the street vendors do not accept the relocation offer from the DPP. Constraints experienced are Personnel Deficiencies, Fleet Weaknesses, and lack of Public Awareness